2014
DOI: 10.3343/alm.2014.34.4.286
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Virulence Genotype and Fluoroquinolone Resistance in Carbapenem-Resistant Pseudomonas aeruginosa

Abstract: BackgroundPseudomonas aeruginosa is a clinically important pathogen that causes opportunistic infections and nosocomial outbreaks. Recently, the type III secretion system (TTSS) has been shown to play an important role in the virulence of P. aeruginosa. ExoU, in particular, has the greatest impact on disease severity. We examined the relationship among the TTSS effector genotype (exoS and exoU), fluoroquinolone resistance, and target site mutations in 66 carbapenem-resistant P. aeruginosa strains.MethodsSixty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 38 publications
5
52
1
1
Order By: Relevance
“…Consistent with the current finding regarding the high prevalence of fluoroquinolone resistance in ExoU isolates (100%), Wong-Beringer et al [38] found that 92% of ExoU were fluoroquinolone-resistant compared with 61% resistance in ExoS. The association between MDR and the presence of the ExoU genotype has been associated with poor clinical outcome in patients with pneumonia in two different studies, particularly in immunocomporomised patients [39,40], with no clear genetic explanation. Proper surveillance for the emergence of the cytotoxic and MDR P. aeruginosa isolates would be essential for preventing serious P. aeruginosa outbreaks in surgical wards.…”
Section: Figsupporting
confidence: 76%
“…Consistent with the current finding regarding the high prevalence of fluoroquinolone resistance in ExoU isolates (100%), Wong-Beringer et al [38] found that 92% of ExoU were fluoroquinolone-resistant compared with 61% resistance in ExoS. The association between MDR and the presence of the ExoU genotype has been associated with poor clinical outcome in patients with pneumonia in two different studies, particularly in immunocomporomised patients [39,40], with no clear genetic explanation. Proper surveillance for the emergence of the cytotoxic and MDR P. aeruginosa isolates would be essential for preventing serious P. aeruginosa outbreaks in surgical wards.…”
Section: Figsupporting
confidence: 76%
“…In this study, all of the isolates showed at least one of the exotoxin and the prevalence of exoU (5). These findings are contrary to our results.…”
Section: Discussioncontrasting
confidence: 57%
“…The type III secretion system (TTSS) has been known to be a major virulence, which is determined in pathogenesis of acute infection, bacteremia, sepsis and subsequent mortality. The TTSS allows the injection of toxins into the cytosol of target eukaryotic cells, where they destroy host cell defense and signaling systems and that subsequently rapid call necrosis or modulating the actin cytoskeleton (4)(5)(6). Four effector proteins have been identified: ExoU, which is a phospholipase and it has been characterized as a major virulence factor in acute lung injury, ExoY that is an adenylate cyclase, and ExoS and ExoT which are bifunctional proteins (5,6).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations